Psychosocial factors and indoor environmental quality in respiratory symptom reports of pupils: a cross-sectional study in Finnish schools - Juha Pekkanen; Kateryna Savelieva; Marko Elovainio; Jussi Lampi; Sari Ung-Lanki (BMJ Open, 2020)
Objectives Poor indoor environmental quality (IEQ) in schools is related to higher respiratory symptoms of pupils, but little is known about the importance of other factors. This study examined the associations between different psychosocial factors and other pupils’ individual and allergic characteristics, beyond school IEQ, and reporting of respiratory symptoms in pupil-administered and parent-administered questionnaires.Setting All primary and secondary schools in two areas of Helsinki, Finland.Participants Primary school pupils (grade 3–6, n=8775, 99 school buildings) and secondary school pupils (grade 7–9, n=3410, 30 school buildings) reported their respiratory symptoms, as well as psychosocial factors and individual characteristics. Parents of primary school pupils (grade 1–6, n=3540, 88 school buildings) also filled in questionnaires, but the response rate was low (20% in 2017 and 13% in 2018).Main outcome measure Respiratory symptoms were reported in relation to the school environment and in general (without such relation) by pupils or parents.Results Worry about IEQ and low school satisfaction, and asthma and hay fever were related to higher reporting of respiratory symptoms in three samples. The variance between schools in respiratory symptoms was low (intraclass correlation=0.6%–2.4%). Psychosocial factors, especially worry about school’s IEQ, explained more of the variance between schools in symptoms than IEQ among secondary school pupils and parents, but not among primary school pupils for symptoms in general. Worry about IEQ also modified the associations between IEQ and respiratory symptoms, but only in parental reports.Conclusion In addition to IEQ, psychosocial factors and pupils’ individual and allergic characteristics were related to higher reporting of respiratory symptoms in all three samples. Psychosocial factors explained more variance between schools than IEQ, although it was 2.4% at most. Other factors beyond IEQ should be considered when interpreting symptom reporting in indoor air questionnaires.